Significance of idiopathic deep venous thrombosis. Issue 702 (April 1984) - O'Connor, N. T.; Cederholm-Williams, S. A.; Fletcher, E. W.; Allington, M.; Sharp, A. A.
Abstract : The risk of developing an overt malignancy after an isolated deep venous thrombosis (DVT) is poorly documented. We therefore reviewed a series of patients in whom a solitary idiopathic DVT had been proven by venography at least 12 months earlier. No patient had developed a malignancy at follow-up. However, decreased fibrinolytic activity was observed in five out of the six patients aged less than 45 years. Patients with an idiopathic DVT should not be subjected to an exhaustive search for malignancy.